PEMBERDAYAAN APARAT PEMERINTAH KELURAHAN LOK BAHU DALAM MELAKSANAKAN ADMINISTRASI KEPENDUDUKAN - Jaini . (Jurnal Paradigma (JP), 2017)
This study suggests that the ability of urban authorities in implementing the population administration is still not enough, it is because lack of empowerment officers through providing opportunities for education and training, in addition to the inadequacy of the budget and operational funding.